Mediation Effects of Social Self-Efficacy and Fear of Negative Evaluation on the Influence of Shyness on Depression - Su-Mei, Su (Jiao yu ke xue yan jiu qi kan, 2017)
The purpose of this study was to explore the mediation effects of social self-efficacy and fear of negative evaluation on the influence of shyness on depression. The subjects were 407 undergraduates in Taiwan. Structural equation modeling was used to analyze the data. The following results were revealed: (1) Shyness has a direct negative effect on undergraduates’ social self-efficacy and a direct positive effect on fear of negative evaluation. (2) Social self-efficacy has a direct negative effect on undergraduates’ depression. Fear of negative evaluation has a positive direct effect on depression. (3) Social self-efficacy and fear of negative evaluation mediate the relationships between shyness and depression. Suggestions and implications for education, counseling, and future research are discussed.